The Supply Chain Process of Environmental Information System in the Malaysian Manufacturing Industry - Habidin, Nurul Fadly; Hudin, Norlaile Salleh; Md Zabit, Mohd Nazir; Fuzi, Nursyazwani Mohd; Ong, Sharon Yong Yee (International Journal of Supply Chain Management, 2018)
The purpose of this study is to examine the supply chain process of environmental information system and to develop the supply chain process of environmental information system in the Malaysian manufacturing industry. This study utilized the Statistical Package for Social Sciences Statistics software and Structural Equation Modelling to analyze statistical analysis. This study will used exploratory factor analysis and confirmatory factor analysis to identify the supply chain process of environmental information system and to develop the supply chain process of environmental information system in the Malaysian manufacturing industry. Data will be collected using a questionnaire survey from 2,700 manufacturing companies. Therefore, environmental information system can assist the organization to monitor, improve, and evaluate environmental management in the manufacturing industry.